2011
DOI: 10.1080/02640414.2010.551540
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental movement skill performance of preschool children in relation to family context

Abstract: Evidence suggests the development of fundamental movement skill (FMS) is a key factor in promoting long-term physical activity. Low levels of activity among preschool children and the relationship between physical activity and the development of fundamental movement skills underline the need to determine the factors associated with children's development of such skills. As parents play an important role in the socialization process, the aim of this study was to examine correlates of family and neighbourhood ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 12 publications
12
134
0
6
Order By: Relevance
“…Moreover, it is possible that the socio-economic status of the families of the different regions may also play a moderator/mediator role in GMC levels, though families are rather similar in their SES given that all children/adolescents are in public schools. It has also been suggested that the family context may enable the development of fundamental motor skills and motor coordination, but the available information is only for children below 3 years of age (Barnett, Hinkley, Okely, & Salmon, 2013;Cools, De Martelaer, Samaey, & Andries, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is possible that the socio-economic status of the families of the different regions may also play a moderator/mediator role in GMC levels, though families are rather similar in their SES given that all children/adolescents are in public schools. It has also been suggested that the family context may enable the development of fundamental motor skills and motor coordination, but the available information is only for children below 3 years of age (Barnett, Hinkley, Okely, & Salmon, 2013;Cools, De Martelaer, Samaey, & Andries, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…5 Regrettably, preschools and schools are limiting children's opportunities to learn and develop proficiency in FMS. Ideally, children should develop FMS proficiency during early childhood and primary school through a range of opportunities, including unstructured active play, 6 interactions with parents, siblings and caregivers, 7,8 quality physical education, 9,10 school sport and community-based programs. 11 Yet, many children are entering secondary school lacking proficiency in many FMS.…”
mentioning
confidence: 99%
“…The evidence of this and previous studies suggests that physical activity may be a critical determinant of FMS in day care-aged children (Barnett et al 2013;Fisher et al 2005;Iivonen and Sääkslahti 2013). In light of the research evidence, we suggest that spending a lot of time outdoors, allowing adequate amounts of active free play (Sääkslahti et al 1999), providing access to diversified physical environments (Fjørtoft 2001) and raising parental awareness of the importance of physical activity for their child (Barnett et al 2013;Cools et al 2011) are among the important factors to be considered when designing motor skill-promoting strategies in the day care setting. We also think that education in the importance of motor skill development for children's wellbeing and overall development and knowledge of the circumstances that facilitate physical activity should be important part of early childhood education programs (Tremblay et al 2012).…”
Section: Relationships' Complexitymentioning
confidence: 55%
“…A Norwegian study indicated that playing in the forest near the day care centre versus inside the center's perimeter fence positively affected children's balance and coordination (Fjørtoft 2001). Cools et al (2011) found that parents' physical activity and high value placed on their child's sportspecific physical activity were positively associated with children's FMS performance ). An Australian study indicated that although a number of family and environmental factors were positively associated with children's locomotor and manipulative skill proficiency, only child-level factors were significant (i.e.…”
Section: Introductionmentioning
confidence: 95%